A Comparative Study of Leadership Factors Affecting Public and Private Sector Banks in India: An Employee Perspective - Swain, Hirapunyatirtha; Mohapatra, Sunita (Prabandhan: Indian Journal of Management, 2013)
In the scenario of cutthroat competition and changing business models, employee motivation is the key driver of organizational effectiveness. Among many factors that impact employee motivation, leadership is one of them, not only at the top level, but at every stage of functioning. The study highlights the underlying dimensions of employee- perceived leadership in Indian banking sectors as well as compares and contrasts the leadership perceptions between the public and private sector banks. The data was collected through a structured questionnaire from both the public and private sector bank employees and was analyzed by using SPSS to make it informative. The results reveal that employees of public sector banks perceived their leaders as Rule-based-task-oriented and Committed-withcentralized-authority, whereas employees of private sector banks perceived their leaders as Integrated-higher-task-performing and Rule-based-submissive-authoritarian. It was also found that the employees of public sector banks perceived their leaders as more Nurturing, Autocratic, and Bureaucratic, whereas the employees of private sector banks perceived their leaders to be more Task-Oriented and Participative by nature.